Simplified model-free predictive current control for dual air-gap transverse-flux six-phase permanent magnet electric machines - Hsing-Cheng Yu; Hao-Cheng Chuang; Zhao Ming Wang; Cheng-Kai Lin (Advances in Mechanical Engineering, 2017)
A novel dual air-gap transverse-flux six-phase permanent magnet electric machine using C-shaped configured architecture with laminated silicon steel is designed and implemented in this study. The magnetic flux density distribution and magnetic flux linkage of the C-shaped configured architecture with laminated silicon steel have been achieved to verify the design concept which leading the magnetic line in the same direction as laminated silicon steel arrangement. The notches on both stators and rotors are designed aiming at lowering down cogging torque and compared with a normal permanent magnet electric machine. The optimal combination is resulted in the cogging torque reduction of 70.2%, and the output torque reduction is 6.5%. Additionally, a new model-free predictive current control, insensitive to parameter variations of the electric machines, is proposed to drive the permanent magnet electric machine aiming at six-phase current error reduction within 0.36 A. As a result, a better satisfactory current tracking ability of the proposed model-free predictive current control law in the six-phase permanent magnet electric machine has been validated successfully in experimental results.